Multi-Objective User Preference Enabling Method for Service Restoration in Distribution Networks with High Renewable Energy Penetration. Issue 1 (9th August 2021) - Jia, Lulu; Chiang, Hsiao-Dong; Wang, Zhi-Yuan
Abstract: Service restoration (SR) in distribution networks by nature is a multi-objective optimization problem. To solve the multi-objective SR and to ensure sufficient available delivery capability for delivering renewable energy, a user preference enabling (UPE) method is proposed in this paper. The proposed method is user-oriented, allowing a user's preferred solution over a range of each objective function value to be achieved. The proposed UPE method can adopt each user's specific preference over each objective function, allowing the user to directly place a preference for each objective function without compromising their independence from each other. If the user preference problem has no solution, the proposed method will identify the non-existence of a solution and suggest a remedy scheme to recover a solution. To achieve its computational efficiency, the proposed UPE method contains a discrete optimization stage and a relaxation and correction stage to solve the multi-objective SR problem, which has a large number of binary variables. A user-preferred solution that truly meets the user's needs for each objective is thus fast obtained. The effectiveness and flexibility of the proposed UPE-based method is evaluated on large distribution networks with multiple scenarios.